POTENSI PHOTODINAMIK INAKTIVASI Staphylococcus aureus DAN Vibrio cholerae DENGAN ENDOGEN PHOTOSENSITIZER PADA PENYINARAN LED BIRU (430 ± 4) nm DAN MERAH (629 ± 6) nm - Suryani Dyah Astuti; Djoni Izak R.; Ni’matuzahroh; M. Zainuddin; Suhariningsih (The East Java Biological Society, 2011)
Photodynamic Inactivation (PDI) is bacteria inactivation method with using light and bacteria porphyrin photosensitizer.The combination of light and photosensitizer with suitable spectrum can promote photosensitization process and then cause bacteria photodamage. This research was laboratory experiment, to analyze photodamage potency of Gram positive bacteria Staphylococcus aureus and Gram negative Vibrio cholera with combination of endogen photosensitizer and LED exposure (blue LED (430 ± 4) nm and red LED (629 ± 6) nm)) on Pulse Width Modulation (PWM) 75% and time duration 30 minutes. The viability of bacteria had been counted after 48 hours incubation on temperature 37oC by using Total Plate Count (TPC). Result of this research showed that blue LED exposure (430 ± 4) nm had potency to decrease 70% Staphylococcus aureus and 50% Vibrio cholera bacteria colony forming unit. Red LED (629 ± 6) nm exposure decreased 22% dan 3% colony forming unit. So blue LED exposure had big potency to bacteria inactivate.